Changes of Soil Chemistry Characteristics of Tephra Mount Anak Krakatau-Indonesia, Through Leaching Experiment - Astriana Rahmi Setiawati; Jamalam Lumbanraja; Ananda Ika Kurnia; Manarul Hidayat; Septi Nurul Aini; Dedy Prasetyo (JOURNAL OF TROPICAL SOILS, 2023)
Studying the weathering process in pristine volcanic materials is crucial as this process will determine further soil characteristics. Mount Anak Krakatau is reported as one of the fastest-growing volcanoes. This volcano erupted powerfully in December 2018, ejecting tons of volcanic materials. These materials are considered pristine and unweathered tephra. Hence, a leaching experiment can be one of the crucial methods to predict further soil characteristics formed as climatic factors. Tephra sampling was conducted on 13 Augustus 2019 or eight months after the massive eruption of Mount Anak Krakatau in December 2018. Tephra samples were leached by deionized water (H2O), oxalic acid (H2C2O4) 0.02 M, and citric acid (C6H8O7) 0.02 M (solvents) for 90 days. pH of tephra increased approximately from  (3.95– 4.99 ) to (5.12–8.11). Organic-C rose about 0.2 to 1 point higher than organic-C of tephra before the leaching experiment. The increasing value of organic-C was predicted to increase CEC (Cation Exchange Capacity) (2.13–5.36 cmolc kg-1). After the leaching experiment, the tephra’s surface was weathered clearly as an impact of solvents and the growing of algae.